HUBUNGAN KARAKTER DISIPLIN DENGAN KEMAMPUAN BERFIKIR SISWA DALAM KEGIATAN PEMBELAJARAN EKONOMI DI SMAN 2 SINGINGI - Emilia Susanti; Almegi (Perspektif Pendidikan dan Keguruan, 2020)
This study aims to determine the relationship between the character of discipline and students 'thinking skills in economic learning activities at SMAN 2 Singingi which is motivated by the students' low ability to think in economic learning activities at SMAN 2 Singingi. This type of research is quantitative research. Subjects in the study of the relationship of character education with thinking skills of students in economic learning activities. Data collection techniques in this study used questionnaires, documentation and tests. The data analysis technique used is the correlation test using the Produck moment correlation formula. Based on the corelation test results obtained by Person Corelation value of 0.727 this means that there is a strong relationship between the character of discipline with students' thinking ability on economic subjects at SMAN 2 Singingi. this is also done by comparing r Count with r Table where (1% 0.727> 0.232), (5% 0.727> 0.275). Then it can be concluded that Ha is accepted and Ho is rejected and from the results of the hypothesis test above it can be concluded that there is a significant relationship between the character of discipline and students' thinking ability on economic subjects at SMAN 2 Singingi.